The Impact of Known Criminogenic Factors on Offenders with Intellectual Disability: Previous Findings and New Results on ADHD. Issue 1 (18th December 2012) - Lindsay, William R.; Carson, Derek; Holland, Anthony J.; Taylor, John L.; O'Brien, Gregory; Wheeler, Jessica R.
<x xml:space="preserve">Abstract</x> Background Developmental and index offence variables have been implicated strongly in later criminal behaviour and service pathways and this paper investigated attention deficit hyperactivity disorder (ADHD) which, with conduct disorder, has emerged from previous studies on offenders. ADHD and conduct disorder are over‐represented among criminal populations when compared to the general population. The present authors reviewed the extent to which ADHD affected the presentation of offenders with intellectual disability. Method Information related to index behaviour, history of problem behaviours, childhood adversity and psychiatric diagnoses was recorded in 477 referrals to forensic intellectual disability services. Comparisons were made between those with a previous diagnosis of ADHD and those without. Results The ADHD group showed higher proportions of physical aggression, substance use, previous problems including aggression, sexual offences and property offences, birth problems and abuse in childhood. Effect sizes were small. Conclusion Attention deficit hyperactivity disorder with conduct disorder is associated with a greater degree and history of problematic behaviour in offenders with intellectual disability.